2019
DOI: 10.1111/cpr.12610
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA cMras inhibits lung adenocarcinoma progression via modulating miR‐567/PTPRG regulatory pathway

Abstract: Objectives: Circular RNA, a type of RNA formed by a covalently closed loop, possesses sophisticated abilities of gene regulation in tumorigenesis and metastasis.However, the role of circRNAs on lung adenocarcinoma (LUAD) remains largely unknown. Materials and methods:The role of cMras was examined both in vitro and in vivo.cMras expression in LUAD tissues was determined by quantitative real-time PCR (qRT-PCR). Downstream targets of cMras were predicted by bioinformatics tools and confirmed by RNA immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…The known STAT3-binding phosphatases are receptor-type PTPs such as PTPRK, PTPRD, and PTPRK and nonreceptor PTPs, including SHP1, SHP2, PTP-MEG2, and TC-PTP. These PTPs are frequently mutated or inactivated in lung cancer, colorectal cancer, glioblastoma, head and neck squamous cell carcinomas, and renal cell carcinoma 21,23,24,[44][45][46] , suggesting that their inactivation contributes to the malignancy of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The known STAT3-binding phosphatases are receptor-type PTPs such as PTPRK, PTPRD, and PTPRK and nonreceptor PTPs, including SHP1, SHP2, PTP-MEG2, and TC-PTP. These PTPs are frequently mutated or inactivated in lung cancer, colorectal cancer, glioblastoma, head and neck squamous cell carcinomas, and renal cell carcinoma 21,23,24,[44][45][46] , suggesting that their inactivation contributes to the malignancy of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, our data also indicated that miR‐567 might be a tumour suppressor in RCC cells. Noteworthy, a recent study reported that miR‐567 could be sponged by circRNA cMars and inhibition of miR‐567 contributed to the progression of lung adenocarcinoma 23 . This discrepancy might be caused by different tumour tissues, thereby more investigations regarding the function of miR‐567 are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Patients could have totally different final outcomes although they might possess similar clinical and pathological types [ 20 ]. The development of next-generation sequencing promoted the preclinical application of bioinformatics [ 21 , 22 ], which could comprehensively combine the gene profiling with the clinical parameters. Compared with the tumor-node-metastasis (TNM) system, it has been confirmed among various types of cancers that the prognostic signature could improve the accuracy of prediction [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%